The role of cone beam computed tomography in creating of the minimally invasive endodontic access in multyrooted teeth (Эндодонтия Today, 2020)
A method is presented that allows creating plastic patterns in the laboratory using computer tomography data, laser surface scanning of teeth, as well as a number of computer programs, the use of which in endodontic dentistry can accurately determine the topographic dimensions of their coronary cavities. The use of this method in the clinic will significantly save the loss of hard tissues of teeth when creating endodontic access.